Mangrove bird community of Paranaguá Bay - Paraná, Brazil - Luiz Augusto Macedo Mestre (Brazilian Archives of Biology and Technology, 2007)
This study describes the mangrove bird community of Paranaguá Bay in Paraná - South Brazil. Seasonal surveys were conducted during September 1997 to September 1998 at three sites in Paranaguá Bay. Frequencies and abundances of birds were registered in 200m transects and one hour point counts. A total of 81 bird species were observed in the three sampling sites. Most of the bird species in Paranaguá mangroves are fruits, seeds and arthropods consumers, and predators of flying insects. The most frequent and abundant species were Egretta caerulea, Ceryle torquata, Chloroceryle amazona, Pitangus sulphuratus, Turdus amaurochalinus and Parula pitiayumi. The bird community of these three sites is composed mainly by forest bird species. The mangroves of Paranaguá Bay shelter one of the richest avifauna of Brazilian mangroves. Differences between sampling sites could be related to the proximity of the Paranaguá city and human impacts in the areas. Only in the most disturbed site were observed Passer domesticus and large flocks of Coragyps atratus. This study contributed to the knowledge of mangrove communities, and could be an important basis to fluvial-marine conservation plans in Paraná- Brazil. Este estudo teve como objetivos caracterizar a comunidade de aves de manguezais na baía de Paranaguá e comparar descritivamente a comunidade das três áreas amostradas, diferentes em relação à proximidade de centros urbanos. Foram amostradas sazonalmente, entre setembro de 1997 a setembro 1998, três áreas de manguezais a diferentes distâncias da cidade e do porto de Paranaguá. A avifauna foi registrada em transectos de 200m no interior dos manguezais e em observações de 1 hora em pontos fixos. Foram determinadas freqüência, abundancia relativa e densidade de espécies em cada área. Foram observadas 81 espécies de aves nas três áreas de manguezais. As guildas mais significativas foram das espécies consumidoras de frutos, sementes e artrópodos de copa e das predadoras de insetos em vôo. As espécies mais freqüentes e abundantes foram Egretta caerulea, Ceryle torquata, Chloroceryle amazona, Pitangus sulphuratus Turdus amaurochalinus e Parula pitiayumi. Esta comunidade é uma das mais ricas dos manguezais brasileiros atualmente estudados e se destaca por ser composta principalmente por aves que também ocorrem nas florestas de restinga ao redor. Algumas diferenças entre as áreas amostradas podem ser decorrentes dos impactos ocasionados pela proximidade dos centros urbanos. Além de contribuir significativamente para o conhecimento deste ecossistema, os resultados do presente estudo poderão servir de base para planos de conservação dos ambientes de influencia flúvio-marinha no estado do Paraná.